Exploration of the experiences of breastfeeding doctors within the Cape Town Metropole District health service - Davids, Tina (Department of Public Health and Family Medicine, 2025)
Exclusive breastfeeding in the first six months of life is known to be associated with many positive health outcomes. The regulatory environment in South Africa supports this, which has resulted in an improvement in exclusive breastfeeding from 7% in 2003, to 31.6% in 2016. However, it is not known how physician-mothers, who are themselves wanting to breastfeed, have experienced this phenomenon in their respective workplaces. This study explored the breastfeeding (BF) or breastmilk expression (BME) experience of doctors within the Cape Town Metro District Health Service. Aim: To describe the breastfeeding experiences, expectations, intentions, and outcomes of breastfeeding within the workplace. Methods: we conducted a qualitative cross-sectional study using semi-structured interviews. Data was analysed thematically, using an inductive approach. Results: Interviews with ten (N=10) participants were conducted, reaching data saturation after the eigth interview. The varying perspectives are reported within key themes that emerged: BF/BME aspirations at work; Awareness of existing breastfeeding policy; Enabling factors to BF/BME within the workplace; Barriers to BF/BME within the workplace. Conclusion: This novel exploratory study identified key factors that facilitate or hinder BF/BME within the workplace in this context. Recommendations to enhance BF/BME practices at work are made, based on implementing the existing policy. Pathways for future research are proposed that focus on improving the person-centred orientation of health services.